Association of Neighborhood Walkability With Change in Overweight, Obesity, and Diabetes - Creatore, Maria I; Glazier, Richard H; Moineddin, Rahim; Fazli, Ghazal S; Johns, Ashley; Gozdyra, Peter; Matheson, Flora I; Kaufman-Shriqui, Vered; Rosella, Laura C; Manuel, Doug G; Booth, Gillian L (JAMA : the journal of the American Medical Association, 2016)
Rates of obesity and diabetes have increased substantially in recent decades; however, the potential role of the built environment in mitigating these trends is unclear. To examine whether walkable urban neighborhoods are associated with a slower increase in overweight, obesity, and diabetes than less walkable ones. Time-series analysis (2001-2012) using annual provincial health care (N ≈ 3 million per year) and biennial Canadian Community Health Survey (N ≈ 5500 per cycle) data for adults (30-64 years) living in Southern Ontario cities. Neighborhood walkability derived from a validated index, with standardized scores ranging from 0 to 100, with higher scores indicating more walkability. Neighborhoods were ranked and classified into quintiles from lowest (quintile 1) to highest (quintile 5) walkability. Annual prevalence of overweight, obesity, and diabetes incidence, adjusted for age, sex, area income, and ethnicity. Among the 8777 neighborhoods included in this study, the median walkability index was 16.8, ranging from 10.1 in quintile 1 to 35.2 in quintile 5. Resident characteristics were generally similar across neighborhoods; however, poverty rates were higher in high- vs low-walkability areas. In 2001, the adjusted prevalence of overweight and obesity was lower in quintile 5 vs quintile 1 (43.3% vs 53.5%; P < .001). Between 2001 and 2012, the prevalence increased in less walkable neighborhoods (absolute change, 5.4% [95% CI, 2.1%-8.8%] in quintile 1, 6.7% [95% CI, 2.3%-11.1%] in quintile 2, and 9.2% [95% CI, 6.2%-12.1%] in quintile 3). The prevalence of overweight and obesity did not significantly change in areas of higher walkability (2.8% [95% CI, -1.4% to 7.0%] in quintile 4 and 2.1% [95% CI, -1.4% to 5.5%] in quintile 5). In 2001, the adjusted diabetes incidence was lower in quintile 5 than other quintiles and declined by 2012 from 7.7 to 6.2 per 1000 persons in quintile 5 (absolute change, -1.5 [95% CI, -2.6 to -0.4]) and 8.7 to 7.6 in quintile 4 (absolute change, -1.1 [95% CI, -2.2 to -0.05]). In contrast, diabetes incidence did not change significantly in less walkable areas (change, -0.65 in quintile 1 [95% CI, -1.65 to 0.39], -0.5 in quintile 2 [95% CI, -1.5 to 0.5], and -0.9 in quintile 3 [95% CI, -1.9 to 0.02]). Rates of walking or cycling and public transit use were significantly higher and that of car use lower in quintile 5 vs quintile 1 at each time point, although daily walking and cycling frequencies increased only modestly from 2001 to 2011 in highly walkable areas. Leisure-time physical activity, diet, and smoking patterns did not vary by walkability (P > .05 for quintile 1 vs quintile 5 for each outcome) and were relatively stable over time. In Ontario, Canada, higher neighborhood walkability was associated with decreased prevalence of overweight and obesity and decreased incidence of diabetes between 2001 and 2012. However, the ecologic nature of these findings and the lack of evidence that more walkable urban neighborhood design was associated with increased physical activity suggest that further research is necessary to assess whether the observed associations are causal.